1642 Va. Acts 261, Act 35 - (:unkn) unknown (My University, 1642)
Be it further enacted and confirmed, for the better observation of the Sabbath and for the restraint of diverse abuses committed in the colony by unlawful shooting on the Sabbath day as aforesaid, unless it shall be for the safety of his or their plantations or corn fields or for defense against the Indians, he or they so offending shall forfeit for his or their first offense being thereof lawfully convicted . . . the quantity of twenty pounds...
Keywords: DISCHARGE